Simultaneously ultrasensitive and differential detection of SARS-CoV-2, adenovirus and influenza a virus using multiplex fluorescence lateral flow immunoassay - Li, Xiaoyan; Zhao, Changxu; Hou, Guangzheng; Sun, Zhihua; Liu, Xiaomei; Ding, Yanlei; Fang, Yi; Liu, Qiqi (Frontiers in Immunology, 2025)
IntroductionThe rapid and precise differential diagnosis of respiratory diseases is crucial to impede the spread of the viruses, considering the substantial demand resulting from frequent co-infectionsMethodA quantum dot nanobeads (QBs)-based multiplex fluorescence lateral flow immunoassay (QBs-based MF-LFA) biosensor was developed. The MF-LFA biosensor enabled simultaneous and sensitive quantification of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), Adenovirus (ADV), and Influenza A Virus (IAV), boasting low limit of detection (LOD) of 56, 120, and 41 copies/mL, respectively. Compared to colloidal gold LFA, the LOD was improved by 200, 417, and 1220 times, respectively, while maintaining sensitivity comparable to PCR techniques.Result and discussionsThe biosensor provided results within 20 minutes, exhibited good reproducibility, and boasted high accuracy with recoveries ranging from 96% to 105%. Additionally, the biosensor had a shelf life of up to 8 months, attributed to the use of freeze-dried probes with minimal water content, ensuring enhanced stability. Clinical samples of SARS-CoV-2, ADV and IAV infections were tested, the results were consistent with both PCR testing and clinical diagnostic tests. This highlights the considerable potential of our biosensor for early and rapid differential detection of respiratory viruses.